I never thought of it that way : how to have fearlessly curious conversations in dangerously divided times - Guzmán, Mónica (Journalist) (BenBella Books, Inc., 2022)
"When you think you have the answers, you need to be asking a lot more questions--and embracing fearless curiosity. In this timely, personal guide, journalist Mónica Guzmán shows why curiosity is our best policy and how you can put it to work for you immediately, sharing practical tips from the trenches of the social, political, and cultural divides"--